151k views
2 votes
Which equation could be used to find the length of the hypotenuse?

6^2+11^2=c^2 6^2+c^2=11^2 c^2-6^2=11^2. 11^2-6^2=c^2

User Chaz
by
5.2k points

2 Answers

4 votes

Answer:

In a shorter explanation its A on edgeniuty

Explanation:

User Frayda
by
5.4k points
1 vote

Answer:

6² + 11² = c²

Explanation:

If we consider a right triangle Δ ABC, whose side AB and side BC are the two perpendicular legs, then AC is considered to be the hypotenuse.

Now, if the length of one leg AB is to be 6 units and the length of the other leg BC is to be 11 units.

Then the length of the hypotenuse, c is given by

AC² = AB² + BC² {Applying Pythagoras Theorem}

⇒ c² = 6² + 11²

6² + 11² = c² (Answer)

User James Kleeh
by
5.9k points